Measuring physician practice site characteristics: A comparison of data from SK&A and a practice site survey. (16th November 2020) - Maurer, Kristin A.; Blue, Laura; Orzol, Sean; Morrison Hensleigh, Nikkilyn; Peikes, Deborah
Abstract: Objective: To evaluate the comparability of commercially available practice site data from SK&A with survey data to understand the implications of using SK&A data for health services research. Data sources: Responses to the Comprehensive Primary Care Plus (CPC+) Practice Survey and SK&A data. Study design: Comparison of CPC + Practice Survey responses to SK&A information for 2698 primary care practice sites. Data collection: CPC + Practice Survey data collected through a web‐only survey from April through September 2017, and SK&A data purchased in November 2016. Principal findings: Information was similar across data sources, although some discrepancies were common. For example, 56% of practice sites had differences in the reported number of practitioners, and larger sites tended to have larger differences. Among practice sites with 1 practitioner in the survey, only 1.3% had a difference of 3 or more practitioners between the data sources, whereas 63% of practice sites with 11 or more practitioners had a difference of 3 or more practitioners. Conclusions: Discrepancies between data sources could reflect differences of interpretation when defining practice site characteristics, changes over time in those characteristics, or data errors in either SK&A or the survey. Researchers using SK&A data should consider possible ramifications for their studies.